2010
DOI: 10.1203/pdr.0b013e3181ca0807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Complete Maternal and Littermate Deprivation on Morphine-Induced Fos-Immunoreactivity in the Adult Male Rat Brain

Abstract: Previous research has demonstrated that rats reared in isolation from their dam and littermates show altered behavioral responsiveness to both natural and drug-mediated rewards. This study examined the effects of complete maternal deprivation through the use of artificial rearing on neural activation after acute morphine exposure in adulthood. Male rats were either artificially reared (AR) or maternally reared (MR) from postnatal day 5 to 21. In adulthood (4 mo old), rats received a single injection of morphin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Pups in the morphine group received morphine subcutaneously (SC) on the back above the tail with additive doses (3,6,9,12,15,18, and 21 mg/kg) every day between 11:00 and 12:00 hr from P8 to P14. These doses were chosen because previous studies reported similar doses (Jones et al, 2002;Rana, Mallet, Robertson, & Wainwright, 2010). Each day, the injected dose of morphine was increased by 3 mg/kg.…”
Section: Morphine Administrationmentioning
confidence: 99%
“…Pups in the morphine group received morphine subcutaneously (SC) on the back above the tail with additive doses (3,6,9,12,15,18, and 21 mg/kg) every day between 11:00 and 12:00 hr from P8 to P14. These doses were chosen because previous studies reported similar doses (Jones et al, 2002;Rana, Mallet, Robertson, & Wainwright, 2010). Each day, the injected dose of morphine was increased by 3 mg/kg.…”
Section: Morphine Administrationmentioning
confidence: 99%